Doses of sulfur at topdressing and organic compost supply at planting in the production, quality and content of macronutrients in lettuce seeds (Bioscience Journal, 2022)
The purpose of this study was to evaluate doses of sulfur applied at topdressing, with and without organic compost supply at planting, in the production, physiological quality and content of macronutrients in lettuce seeds. Ten treatments were evaluated in a 5x2 factorial scheme (five sulfur doses at topdressing x with and without application of organic compost at planting). The experimental design was a randomized block design, with four replicates. The sulfur doses applied at topdressing fertilization were 50, 100, 150 and 200 kg ha-1 of S, in addition to the control treatment (dose zero). Regarding the treatments with organic compost, the dose of 70 t ha-1 of compost (wet basis) was supplied at planting. The following characteristics were evaluated: seed production (mass and number of seeds per plant), seed quality (mass of one thousand seeds, first count of the standard germination test, germination percentage, and germination speed index) and content of macronutrients and mineral accumulation. The organic compost supply at planting increased seed production by 43% compared to the treatment without the application of organic compost, while the doses of sulfur did not affect the production of lettuce seeds. The supply of organic compost increased the accumulation of a great part of the macronutrients, except for the accumulation of calcium. The lettuce seeds quality was not affected by both the main treatments, the sulfur doses at topdressing and the organic compost supply at planting. The descending order of nutrients accumulated in the lettuce seeds was nitrogen> potassium> phosphorus> magnesium> calcium> sulfur.